Odpowiedź:
1a) 2(3+1)= 8 Prawda
1b) 2(3*3+1)=3(2*3-2) 2*10=3*4 Fałsz
1c) 6*3-1 = 3(5*3-4) 18-1=3*(15-4) 17=33 Fałsz
1d) 2(3+6)=4(3*3+3) 2*9=4(9+3) 18= 4*12 Fałsz
2a) 3(4+5)=4(4+2) 3*9=4*6 Fałsz
2b) 2(4+6)=4(3*4+3) 2*10=4*15 Fałsz
2c) 4*4+2=4*4-8 16+2=16-8 Fałsz
3a) 5y-x=3
3-y=x /*5
5y-x=3 (skracamy 5y)
15-5y=5x (skracamy 5y)
-x=3 /*-1
x=3
3-y=x
3-y=3
-y=3-3
y=0
3b) x-4= -2y /*3
17-3x=2y /*-1
3x-12= -6y (skracamy 3x)
-17+3x=2y (skracamy 3x)
-12= -6y /:-6
2=y
17-3x=2y
17-3x=2*2
17-3x=4
-3x=4-17
-3x=-13 /:-3
x=4,3
4a) 5x-2y=8 /*-3
-5x+6y=5
-15x+6y=8 (skracamy 6y)
-5x+6y=5 (skracamy 6y)
-5x=5 /:-5
x=-1
-5x+6y=5
5+6y=8
6y=8-5
6y=3 /:6
y=0,5
4a) x+2y=9
-x-3y=16 /*-1
x+2y=9
x+3y=-16
2y=9 /2
y=4,5
-x-13,5=16
-x=-16+13,5
-x=-2,5
x=2,5